Integration of CSI, Airqual, IPA, and PGCV to Determine Prioritisation of Service Quality on JTA Airlines - Muhammad Ilham Adelino; Meldia Fitri (Jurnal Teknologi, 2021)
The quality of service on low-cost airlines is something that is often questioned by passengers. The purpose of this study is to identify and determine service priority factors to improve service quality on JTA Airlines using the integration of the CSI, AIRQUAL, IPA, and PGCV methods. The results obtained are the level of customer satisfaction at 65.5% and there is still a difference (gap) between expectations and experience. Priority factors are the departure and arrival of aircraft on time, fast and appropriate handling of flight delays, clear compensation procedures, clear and easy-to-understand customer service complaint information, staff and cabin crew more responsive in handling customer complaints, always ready to provide maximum service to passengers, and pay more attention to the age of the aircraft.